1996
DOI: 10.3109/02713689608995145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of insulin on the electroretinogram of bovine retinain vitro

Abstract: The reduction of ERG amplitudes may result from the hyperpolarising effect of insulin reported in other tissues. The findings suggest that insulin may have a regulatory role in retinal activity; however extrapolation of these results to the intact organism is dependent on the presence of insulin in retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…Although no receptors have been identified so far, CART appeared to inhibit voltage-dependent intracellular Ca 2ϩ signaling and attenuated cocaine enhancement of depolarization-induced Ca 2ϩ influx in rat hippocampal neurons (28). Application of insulin to the in vitro bovine retina preparation decreased the amplitudes of the a-and b-waves of the electroretinogram (29). Insulin receptors are widely expressed in the retina (30), and administration of this hormone modified the permeability of voltage-gated K ϩ and Ca 2ϩ channels through receptor-mediated tyrosine phosphorylation, thus modulating the activity of photoreceptors and Müller cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although no receptors have been identified so far, CART appeared to inhibit voltage-dependent intracellular Ca 2ϩ signaling and attenuated cocaine enhancement of depolarization-induced Ca 2ϩ influx in rat hippocampal neurons (28). Application of insulin to the in vitro bovine retina preparation decreased the amplitudes of the a-and b-waves of the electroretinogram (29). Insulin receptors are widely expressed in the retina (30), and administration of this hormone modified the permeability of voltage-gated K ϩ and Ca 2ϩ channels through receptor-mediated tyrosine phosphorylation, thus modulating the activity of photoreceptors and Müller cells.…”
Section: Discussionmentioning
confidence: 98%
“…The decrease in tonic glutamate release from photoreceptors that would presumably accompany decreased activation of I Ca might also minimize the potential for excitotoxic damage to post-receptoral neurons. In addition to possible neuroprotective benefits, the inhibitory effects of insulin on the ERG bwave [9] and rod Ca 2+ channel (described in this study) indicate that insulin could play a neuromodulatory role in regulating synaptic transmission from rods to second-order neurons. Finally, the present results suggest that alterations in retinal insulin levels or sensitivity to insulin, e.g., during diabetes, may affect photoreceptor cell survival and neurotransmission at the first synapse in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…InsRs are located on both the inner and outer segments of vertebrate photoreceptors [8] and insulin has been shown to produce a dose-dependent decrease in the a-and b-waves of the electroretinogram (ERG) [9]. The ERG b-wave reflects the activity of inputs from photoreceptors onto ON depolarizing bipolar cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the rat retina, Johnson et al (2001) found that SRIF reduced Ca 2+ influx into rod bipolar terminals. (Gosbell et al, 1996) and L-type Ca 2+ channels in rod photoreceptors (Stella et al, 2001). The potency of insulin's actions (IC50 = 2 nM) and the effectiveness of an insulin receptor-specific tyrosine kinase inhibitor suggest that receptors for insulin, and not insulin-like growth factor, are responsible for these effects (Stella et al, 2001).…”
Section: Cannabinoids-cannabinoidsmentioning
confidence: 99%